2021
DOI: 10.3390/beverages7020023
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Aqueous Ethanol Binary Mixtures Containing Alcohol-Relevant Taste and Chemesthetic Stimuli

Abstract: Ethanol is a complex stimulus that elicits multiple gustatory and chemesthetic sensations. Alcoholic beverages also contain other tastants that impact flavour. Here, we sought to characterize the binary interactions between ethanol and four stimuli representing the dominant orosensations elicited in alcoholic beverages: fructose (sweet), quinine (bitter), tartaric acid (sour) and aluminium sulphate (astringent). Female participants were screened for thermal taste status to determine whether the heightened oros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
(212 reference statements)
0
3
0
Order By: Relevance
“…The dominant sensations elicited by ethanol, the primary product of fermentation, are nominally aversive (bitterness, burning/tingling, astringency [14][15][16]). Thus, it has been hypothesized that individuals who are more responsive to these sensations consume less alcohol as it is less likely to be pleasant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant sensations elicited by ethanol, the primary product of fermentation, are nominally aversive (bitterness, burning/tingling, astringency [14][15][16]). Thus, it has been hypothesized that individuals who are more responsive to these sensations consume less alcohol as it is less likely to be pleasant.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Higgins and Hayes [17] reported that the intensity of tetralone (a hop extract that is bitter) and pale ale consumption were positively correlated for pale ale consumers, suggesting that for a subset of consumers the bitterness elicited by hops may be desirable. Furthermore, ethanol also elicits sweetness [14][15][16], a sensation that is typically characterized as appetitive [18]. Lanier et al [19] demonstrated that increased sweetness of sampled scotch was associated with an increase in overall alcohol consumption, whereas the opposite was true for the bitterness.…”
Section: Introductionmentioning
confidence: 99%
“…Within the Special Issue, the study developed by Thibodeau & Pickering [1] aimed at understanding the response to ethanol combined with some associated taste and chemesthetic stimuli that could impact the perception of its sensory properties. These authors centered their research on the response to consumption of binary mixtures containing ethanol, but considered some individual characteristics (thermal taster status of the panelists) within the study variables.…”
mentioning
confidence: 99%